ANALISIS KEMAMPUAN MOTORIK HALUS SISWA CEREBRAL PALSY SPASTIK MELALUI KEGIATAN MENGARSIR - Fadhilah Wirda Lathifa; Siti Nuryanah; Arcivid Chorynia Ruby (STKIP Subang, 2024)
Fine motor skills are an important aspect of the development of school-aged children. However, children who suffer from spastic cerebral palsy have weaknesses in their fine motor skills. All children have the right to receive a decent education that can improve their growth and development. One effort to train fine motor skills in children with spastic cerebral palsy is through shading activities to improve coordination of hand movements, finger muscles and the child's ability to concentrate. The focus of this research is on the fine motor skills of students with spastic cerebral palsy through shading activities. This research uses a qualitative approach with descriptive methods. This research uses interview, observation and documentation techniques to describe the fine motor skills of students with spastic cerebral palsy through shading activities. The results of the research showed that the hand movements of students with spastic cerebral palsy experienced development in the pressure of the hand on the assignment sheet and the results of the students' shading on drawing patterns, although within limitations. Through this simple shading activity, it is hoped that it can facilitate and improve small muscles, especially in the movement of students' hands so that when studying at school they can write and be able to carry out other activities smoothly.